Link to session: Turning literacy tutoring into virtual tutoring. Issue 4 (29th September 2022) - Teichert, Laura; Isidro, Elizabeth
Abstract: The COVID-19 pandemic forced universities to quickly move instruction online. Faced with a remote-only mandate, this case study describes a virtual literacy tutoring field placement completed by teacher candidates (TCs) in an elementary education program. While in-person teaching remained their preferences, TCs felt the virtual tutoring experience was positive and helped develop their teaching skills. Instructors observed varying levels of multimodal integration; however, all TCs maintained student engagement and built their online literacy repertoires. Challenges were both foreseen (e.g., technical issues) and beyond TCs' control (e.g., power outages). Distractions in students' homes proved to be the greatest challenge.